Catalytic Nucleic Acids: Biochemistry, Chemical Biology, Biosensors, and Nanotechnology - Ma, Lingzi; Liu, Juewen (Elsevier, 2020)
Since the initial discovery of ribozymes in the early 1980s, catalytic nucleic acids have been used in different areas. Compared with protein enzymes, catalytic nucleic acids are programmable in structure, easy to modify, and more stable especially for DNA. We take a historic view to summarize a few main interdisciplinary areas of research on nucleic acid enzymes that may have broader impacts. Early efforts on ribozymes in the 1980s have broken the notion that all enzymes are proteins, supplying new evidence for the RNA world hypothesis. In 1994, the first catalytic DNA (DNAzyme) was reported. Since 2000, the biosensor applications of DNAzymes have emerged and DNAzymes are particularly useful for detecting metal ions, a challenging task for enzymes and antibodies. Combined with nanotechnology, DNAzymes are key building elements for switches allowing dynamic control of materials assembly. The search for new DNAzymes and ribozymes is facilitated by developments in DNA sequencing and computational algorithms, further broadening our fundamental understanding of their biochemistry.
Keywords: chemistry; biochemistry; biochemistry applications; enzymology; biomolecules; nanotechnology